Focusing X-Rays with Curved Multiplate Crystal Cavity. (4th August 2010) - Chang, Ying-Yi; Chen, Sung-Yu; Weng, Shih-Chang; Chu, Chia-Hung; Tang, Mau-Tsu; Stetsko, Yuriy; Shew, Bo-Yuan; Yabashi, Makina; Chang, Shih-Lin
Abstract : An overview is given of the study on X-ray focusing using the Fabry-Perot type multi-plate silicon crystal cavities consisting of compound refractive lenses. Silicon (12 4 0) is used as the back reflection for cavity resonance at the photon energy of 14.4388 keV. Measurements of focal length of the transmitted beam through the crystal cavities show enhanced focusing effect due to the presence of back diffraction. Also, an incident beam with ultrahigh energy resolution can improve the focusing owing to the wider acceptance angle of the back diffraction. Considerations based on the excitation of dispersion surface within the framework of X-ray dynamical diffraction theory are also presented to reveal the origin of this enhanced focusing.